LEGAL REGULATION OF SHARENTING – THEORETICAL AND PRACTICAL ASPECTS - Novaković, Uroš (Political Review, 2025)
The family as a social category is becoming increasingly susceptible to the influence of social networks, not only as a group, but also through individual members – primarily parents and children. Sharenting as a form of exercising parental rights is a phenomenon of modern times. Provisions on the protection of children from posting content on social networks are contained in the Law on Public Information and Media and the Family Law. In addition to the scarce legal regulation, domestic case law in this area is also lacking. The subject of the analysis was the judgment of the Court of Appeal in Kragujevac, which was also commented on by the Supreme Court of Cassation. Publishing photos of children on the Internet via social networking (sharenting) can be a dangerous activity that a conscientious parent should be aware of. Given that a minor child, especially up to a certain age (e.g., up to 12 years old), cannot be aware of his or her digital identity, parents are the guardians of that identity, which is also manifested through the publication of images and materials on social networks. Although the legal system should recognize, regulate and ultimately respond to violations of children's rights in the digital sphere, its scope is quite limited due to the constant development of new technologies and new social networks.
Keywords: child; child rights; social networks; sharenting; Internet